The experience of breastfeeding supporters working with mothers at the early stage of breastfeeding practice - Muda, Siti Mariam; Rani, Siti Hajiah (International Islamic University Malaysia, 2019)
breastfeeding cessation occurring both for the mother and the newborn. The use of the alternative technique in promoting breastfeeding practice such as traditional body massage was belief can increase breast milk production that encouraged the mother to breastfeed continuously. This study aims to know the experience of traditional massage practitioner who acts as a breastfeeding support group that works with breastfeeding mothers. A total of five participants from Mamacare, LPPKN Kuantan were involved and interviewed. Data were analysed using a thematic analysis. The findings revealed three themes emerged; enjoyed sharing knowledge and breastfeeding technique, vast massage experience and breastfeeding challenges during the services. Traditional massage practitioner as breastfeeding support group members appreciated their practices and enjoyed to provide help for postnatal mothers at their early breastfeeding practice to strengthen infant’s immunisation.